Analytical Hierarchical Process (AHP) Technique in Enterprise Resource Planning Customization Framework for Customers’ Needs - Ashish Chourasia, Saurabh Shandilya (International Journal of Advanced Science and Technology, 2019)
The ERP’s functionality that is included is an indication of how well the system fits the company’s business needs. Modern Enterprise Resource Planning (ERP) systems have their origins in Materials Requirement Planning (MRP I) systems, which were first introduced in the 1960s and have evolved into modern ERP systems. The goals of this particular study will recognizing ERP implementation critical success factors and compare them with principle. With no creating generalization, this particular study might investigate particular variables in-depth and hence, this will provide a clear understanding in this specific place. The AHP technique was used to prioritise the nine customization choices in the ERP customization framework based on the needs of the customers. If the implementing organisation wants to fully profit from ERP, our findings recommend that they take the ERP as is from the vendor. The degree of user customization is assessed in the first study utilising the Analytic Hierarchy Process (AHP). With increased performance, this approach can accurately detect the specific requirement. The Analytic Hierarchy Process based Requirement Customization Framework (AHP-RCF) is offered as an ideal and consistent enterprise resource planning system in the presented study effort. Customization in ERP projects is a dangerous, yet necessary, step that businesses must take in order to connect their acquired ERP solution with their corporate goals and business processes.